1987
DOI: 10.1111/j.1476-5381.1987.tb11288.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the rate of GABA synthesis in regions of rat brain following a convulsion

Abstract: The rate of synthesis of γ‐aminobutyric acid (GABA) in the cortex, hippocampus and striatum of rat brain was assessed by measuring the linear rate of accumulation of GABA following injection of amino‐oxyacetic acid (AOAA). Five min after a single electrically induced seizure there was a rise in GABA content in these brain regions and an almost total inhibition of the rate of synthesis. Five min after seizure induced by the inhalant convulsant flurothyl there was no rise in GABA content in these brain regions b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
16
0

Year Published

1987
1987
2003
2003

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 17 publications
6
16
0
Order By: Relevance
“…Justification for the use of the method for GABA synthesis measurement has been presented in a preceding paper (Green et al, 1987a (Green et al, 1987a). The degree of synthesis inhibition observed in the striatum in the current study is, in percentage terms, remarkably similar to that observed by the mass fragmentographic approach and extends the previous study by showing that a similar inhibition occurs in the hippocampus.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Justification for the use of the method for GABA synthesis measurement has been presented in a preceding paper (Green et al, 1987a (Green et al, 1987a). The degree of synthesis inhibition observed in the striatum in the current study is, in percentage terms, remarkably similar to that observed by the mass fragmentographic approach and extends the previous study by showing that a similar inhibition occurs in the hippocampus.…”
Section: Discussionsupporting
confidence: 77%
“…The results were obtained by use of the technique of gas chromatography-mass spectrometry (mass fragmentography, Bertillson & Costa, 1976); however, methodological strictures including the precursor-product assumptions inherent in measuring turnover by infusion oflabelled precursors (see Bertillson & Costa, 1976) precluded the use of the method in examining turnover in brain areas such as the cortex and hippocampus. A later study by Bowdler et al (1983) confirmed and extended the observations that the GABA concentration changes in various brain regions following repeated ECS, but did not measure 'Author for correspondence; present address: Astra Neuro- The current studies have demonstrated that a single ECS or flurothyl-induced convulsion can induce marked changes in both GABA synthesis (Green et al, 1987a) and release (Green et al, 1987b) in regions of rat brain. An investigation has therefore been made of the effect of repeated seizures on GABA release in regions ofrat brain and on the rate ofGABA synthesis in various brain regions, the latter study being designed to try to confirm and extend an earlier investigation (Green et al, 1978) by use of a different methodology.…”
Section: Introductionsupporting
confidence: 63%
“…The synthesis of GABA in the cortex, hippocampus and striatum was assessed by measuring the accumulation of GABA following an injection of aminooxyacetic acid (AOAA), a method recently described and validated by Green et al (1987). Briefly, animals were injected with chlormethiazole (35mg kg-', i.p.…”
Section: Gaba Synthesismentioning
confidence: 99%
“…271 Particularly, it exerts antidepressant and antimanic effectiveness in resistant mood disorder patients. ECT acutely decreased GABA release or GABA synthesis in rat brain 272,273 and plasma GABA levels in depressed patients. 130 On the contrary, with repeated ECT, increases in GABA release, GABA concentration, and GABA B biding sites have been reported in rat brain.…”
Section: Antipsychoticsmentioning
confidence: 99%